MULTICULTURAL EDUCATION AS AN IMPORTANT PART OF MODERN EDUCATION (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Diversity of cultures is one of the characteristics of modern social life. Development of multicultural education in such an environment is an important task of education. This thesis examines the organization of educational processes in multicultural education by developing appropriate principles. In addition, while studying the theoretical and practical aspects of the methods of developing multicultural competence, the differences and similarities between them were considered.